Does labour mobility reduce disparities between regional labour markets in Germany? - Annekatrin Niebuhr; Nadia Granato; Anette Haas; Silke Hamann (Verein für Socialpolitik, 2010)
Differences in regional labour market conditions are still pronounced in Germany, especially between the Eastern and the Western part. Traditional neoclassical models imply that labour mobility should reduce disparities. In contrast, models that include externalities or selective migration suggest that regional differences might well increase due to interregional migration of workers. We investigate the impact of labour mobility on regional disparities in Germany between 1995 and 2005. Considering the impact of migration as well as commuting, effects on regional wages and unemployment are estimated. Our results suggest that labour mobility tends to reduce disparities; however, we find significant effects on unemployment disparities only.
Keywords: C23; J61; R23; 330; Regional disparities; migration; commuting; Germany